Pelanggaran Pemberitahuan Penyampaian Pendapat dimuka Umum: Studi di Wilayah Hukum Kepolisian resort Kota Banda Aceh - Nasution, Anhar; Megawati, Cut; Saputra, Jummaidi; Iqbal, Muhammad; Nasution, Kausar; Irwansyah, Irwansyah (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Protests or demonstrations are the right for every community or certain group to express their opinions in public by paying attention to procedures and not contrary to laws and regulations. However, there are still several protests that violate the administration of the notification of public opinion submission. The purpose of this study is to examine the factors that cause notification violations and efforts to handle them. This study uses an empirical juridical method (field research) with data collection techniques through interviews. The results of this study are the factors that cause the notification of demonstrations that are not in accordance with the procedures because the participants of the demonstration do not want to be bound by the procedures for the implementation of the notification of demonstrations and because the coordinators who want to avoid being responsible for the demonstrations that occur. The efforts made are by providing socialization of certain communities and groups. It is recommended that protesters can follow the procedures of the provisions of the notification of public opinion submission and the police more regularly in fostering relationships with the community.